Study on effect of plant growth promoting rhizobacteria on sorghum (Sorghum bicolor L.) under gnotobiotic conditions - M. Chiranjeevi; Geeta D. Goudar; Krishnaraj PU; Nagaraju Yalavarthi (Frontiers in Microbiology)
The rhizosphere is enriched with diverse microflora, allowing for delving prospective microorganisms to enhance crop growth and yield for varied soil conditions. Demand for millet growth-promoting microorganisms is a contemporary need for dryland agriculture. Therefore, a detailed survey was conducted in northern Karnataka, India, to identify the millet growing areas, particularly sorghum. The rhizobacteria from the sorghum (Sorghum bicolor L.) were assessed for promoting seed germination using the paper towel method and classified based on their efficiency. The elite isolates were positive for indole-3-acetic acid (IAA), gibberellic acid (GA), phosphate, zinc oxide solubilization, and hydrogen cyanide (HCN) production. The test isolates were antagonistic to Macrophomina phaseolina and Fusarium sp. and inhibited completely. Further evaluation of the cultures on sorghum growth-promoting attributes under pot culture conditions showed that the plants inoculated with PG-152 (Bacillus subtilis) recorded the highest plant height, chlorophyll content, root dry weight, shoot dry weight, and total dry weight under ideal conditions of fertilization. Two isolates, namely, PG-152 and PG-197, performing superior under pot culture conditions, were identified as Bacillus subtilis and PG-197 as Enterobacter sp., respectively, using 16S rDNA analysis. The sequences were allowed to screen open reading frames (ORF) and found several ORFs in Enterobacter cloacae and Bacillus subtilis, respectively. This study found that the rhizosphere is vital for identifying prospective isolates for biocontrol and plant growth-improving microorganisms.